Impact of Prior Statin Use on Reperfusion Rate and Stroke Outcomes in Patients Receiving Endovascular Treatment - Sang-Hwa Lee (MDPI AG, 2021)
Background: We evaluated the impact of prior statin use on successful reperfusion and stroke outcomes after endovascular treatment (EVT). Method: Using consecutive multicenter databases, we enrolled acute ischemic stroke patients receiving EVT between 2015 and 2021. Patients were classified into prior statin users and no prior statin users after a review of premorbid medications. The primary outcome measure was successful reperfusion defined as modified TICI grade 2b or 3 after EVT. Secondary outcome measures were early neurologic deterioration (END) and a 3-month modified Rankin Scale (mRS) score of 0 to 2. Results: Among 385 patients receiving EVT, 74 (19.2%) were prior statin users, who had a significantly higher successful reperfusion rate compared with no prior statin users (94.6% versus 78.8%, p = 0.002). Successful reperfusion and END occurrence were improved according to statin intensity with a dose–response relationship. In multivariate analysis, prior statin was associated with successful reperfusion after EVT (adjusted odds ratio (95% confidence interval) 5.31 (1.67–16.86)). In addition, prior statin was associated with a lower occurrence of END and good functional status. Conclusion: Our study showed that prior statin use before ischemic stroke might improve successful reperfusion and stroke outcomes after EVT.